BIOTECHNOLOGY OF THE USE OF MICROBIOLOGICAL PREPARATIONS IN INCREASING THE YIELD OF PLANTS GROWING IN CLOSED CONDITIONS. (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the importance of microbiological preparations in agriculture, their effect on plant growth and development, their role in increasing soil fertility, and modern biotechnological methods of their application. The advantages of biological preparations over traditional agrotechnical methods are also analyzed.